Challenges with take-home naloxone in reducing heroin mortality: a review of fatal heroin overdose cases in Victoria, Australia. (4th May 2019) - Stam, Nathan C.; Gerostamoulos, Dimitri; Smith, Karen; Pilgrim, Jennifer L.; Drummer, Olaf H.
Abstract: Aim: Take-home naloxone (THN) programs have been implemented in order to reduce the number of heroin-overdose deaths. Because of recent legislative changes in Australia, there is a provision for a greater distribution of naloxone in the community, however, the potential impact of these changes for reduced heroin mortality remains unclear. The aim of this study was to examine the characteristics of the entire cohort of fatal heroin overdose cases and assess whether there was an opportunity for bystander intervention had naloxone been available at the location and time of each of the fatal overdose events to potentially avert the fatal outcome in these cases. Methods: The circumstances related to the fatal overdose event for the cohort of heroin-overdose deaths in the state of Victoria, Australia between 1 January 2012 and 31 December 2013 were investigated. Coronial data were investigated for all cases and data linkage was performed to additionally investigate the Emergency Medical Services information about the circumstances of the fatal heroin overdose event for each of the decedents. Results and Discussion: There were 235 fatal heroin overdose cases identified over the study period. Data revealed that the majority of fatal heroin overdose cases occurred at a private residence ( n = 186, 79%) and where the decedent was also alone at the time of the fatal overdose event ( n = 192, 83%). There were only 38 cases (17%) where the decedent was with someone else or there was a witness to the overdose event, and in half of these cases the witness was significantly impaired, incapacitated or asleep at the time of the fatal heroin overdose. There were 19 fatal heroin overdose cases (8%) identified where there was the potential for appropriate and timely intervention by a bystander or witness. Conclusion: This study demonstrated that THN introduction alone could have led to a very modest reduction in the number of fatal heroin overdose cases over the study period. A lack of supervision or a witness to provide meaningful and timely intervention was evident in most of the fatal heroin overdose cases.